ON LOCAL SELF-GOVERNMENT AND ITS CONSTITUTIONAL POSITION IN SERBIA - Lapčević, Milivoje; Rapajić, Milan (Law - Theory and Practice, 2023)
Local self-government is a form of decision-making and governance in local communities established on smaller parts of state territories. It is exercised either directly by its citizens, or by their elected representatives, as well as by other local bodies. The local authority, executed by local bodies, theoretically represents the government of citizens in local communities. Local self-government can be considered as the basic organization of power, and the history of constitutionalism cannot be imagined without it. In this paper, the authors first present the basic characteristics of self-government. These include: 1) the existence of a defined scope for certain local self-government activities, executed by local government bodies without interference from the central government; 2) citizens’ entitlement to choose their representatives in local communities through direct elections or to be directly involved in making decisions on important topics of interest to the local community; 3) local institutions’ independence in terms of their organization and personnel; 4) local selfgovernment having its own independent financing sources (taxes, own property); 5) local autonomy protected by the constitution and laws to ensure the unobstructed work of local self-government. In this paper, the authors analyze the elements of the constitutional position of local self-government in Serbia, including its concept, the method of decision-making, jurisdiction, the right to self-organization, and the protection of local self-government.